CHOOSING PARENT MATERIAL OF GRASS PEAVINE (LATHIRUS SATIVUS L.) FOR CREATING DROUGHT RESISTANT VARIETIES - Sylenko, S. I.; Yeremko, L. S.; Sylenko, O. S.; Rohovyi, O. Yu.; Andrushchenko, O. V.; Hanhur, V. V. (Scientific Progress & Innovations, 2020)
One of the ways for stabilization of plant origin protein production under the conditions of global warming is expanding sown areas of leguminous crops, which are characterized by a high adaptive ability to the effect of unfavorable abiotic environmental factors. Grass peavine (Lathirus sativus L.) occupies one of the leading places among these crops and it is characterized by such biological peculiarities as symbiotic relationships with Rhizobium bacteria, the ability to fix molecular nitrogen of the atmosphere, extremely high tolerance to periodic flooding and lack of soil moisture, its salinity, and also resistance to pests and diseases. Among grain leguminous crops grass peavine occupies the second position after chickpeas in terms of drought tolerance. In the initial stages of plant growth and development and during the formation of the vegetative mass, grass peavine had a weak response to moisture deficiency in the soil. The effect of drought was more pronounced during periods of flowering, bean formation and grain filling. The influence of unfavorable abiotic factors was reflected in all periods of the plant productivity formation. In this regard, an important task of the selection process was a comprehensive evaluation of samples, in order to select the most stable ones for the effects of arid conditions at all stages of growth and development. The aim of the research was the evaluation of collection grass peavine samples as to their drought resistance and identification of valuable sources in order to involve them in the selection process. To study the genetic diversity of grass peavine collection, the samples were studied according to the following indicators: drought susceptibility index, tolerance index, average yield, yield stability index, yield index, stress tolerance index and geometric average yield; seed germination method in sucrose solution was also studied. According to results of the conducted evaluation, four grass peavine samples were identified, which confirmed their drought resistance in field and laboratory studies. These samples can be involved in breeding programs to create highly adaptive varieties (UD0400060 from Afghanistan; UD0400078, UD0400080 from Ethiopia, and UD0400719 from Tunisia).